Studi Literature: Strategi Pemasaran Rumah Sakit Untuk Meningkatkan Pendapatan Dan Kualitas Layanan Kesehatan - Rilly Lesnussa; Dety Mulyanti (Jurnal Kesehatan Amanah, 2023)
The hospital as a health service institution for the community has its own characteristics that are influenced by developments in health science, technological advances, and the socio-economic life of the community which must continue to be able to improve services that are of a higher quality and are affordable to the community in order to realize the highest degree of health. In this case the hospital is also a managerial process of people getting what they want and need through creating and exchanging the services offered and quality value to patients. The purpose of this literature study is to find out how marketing strategies are carried out to increase income and quality of health services. The method used is a theoretical review by analyzing and comparing existing theories. The results of this literature study are by selecting the intended consumers (targets), identifying consumer desires, and determining the marketing mix (marketing mix). It can be concluded that the marketing strategy for hospitals and other health facilities is not much different from the marketing strategy in general. Because the strategy aims to promote and introduce hospitals and services provided to increase income and quality of health services. For instant hospitals, a marketing strategy is needed that is good and reliable and able to convince patients both internally and externally so that positive mutual understanding is established in improving the quality of patient services.